Two Rare Cases of Feline Toxic Epidermal Necrolysis: A Novel Therapeutic Approach With Medical-Grade Honey - Alexandra Peteoacă; Niels A. J. Cremers; Linsey J. F. Peters (Case Reports in Veterinary Medicine)
Toxic epidermal necrolysis (TEN) is an acute and life-threatening dermatological condition that is drug-induced and characterized by extensive epidermal detachment. These lesions should be protected from infection using a product that has a low risk of reactivity. Medical-grade honey (MGH) exerts antimicrobial and wound-healing effects while posing a low risk of exacerbating TEN. In this case report, we are the first to describe the use of MGH for wound management in two feline TEN patients. Case 1 involved a 1-year-old female British shorthair cat, while Case 2 featured a 1-year-old female mixed-breed cat. Both patients presented to the hospital with various symptoms, including fever, tongue lesions, and lesions in the abdominal area following ovariohysterectomy surgery. TEN was confirmed via histopathological examination. The suspected cause of TEN in both cases was the iodine present in the surgical scrub. Tongue lesions were addressed with a liquid diet, and all xenobiotics were immediately withdrawn as a precaution. MGH products supplemented with vitamins were applied to the abdominal wounds following a wound lavage with Ringer’s lactate. Daily dressing changes were performed without discomfort, pain, or any adverse reactions. In both cases, debridement became evident after just 1 day, and the patients fully recovered after 12 days of MGH therapy. This case report demonstrates for the first time the successful use of supplemented MGH for wound management in veterinary patients with TEN. The patients did not have any adverse reactions to the treatment, while MGH dressings provided antimicrobial protection and wound-healing effects. Furthermore, these cases highlight the importance of rapid diagnosis and immediate drug withdrawal to increase the survival rate. Overall, supplemented MGH is a safe and effective method to treat TEN-related lesions in feline patients.